2017
DOI: 10.1590/s0004-2803.201700000-09
|View full text |Cite
|
Sign up to set email alerts
|

Sim Brasil Study - Women’s Gastrointestinal Health: Gastrointestinal Symptoms and Impact on the Brazilian Women Quality of Life

Abstract: Gastrointestinal symptoms are highly prevalent in Brazilian women and negatively impact different aspects of quality of life (mood, concentration and sexuality). The bowel is an important emotional catalyst that can modulate the psychologic behavior. Better understanding of the interaction between the gut and the brain should help in the management of gastrointestinal symptoms to improve women's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(81 reference statements)
1
5
0
1
Order By: Relevance
“…Our study found that the lactose intolerant women presented a greater frequency for gastrointestinal symptoms than men. Similar results were evidenced in a Dutch study (21) , in which from a sample consisting of 16.758 individuals, 26% reported having gastrointestinal symptoms with a high prevalence of females (66%), and also in a Brazilian study by Del'Arco and collaborators (22) . Differences between the sexes in intestinal motility and visceral sensibility have already been suggested in the literature as factors associated with the higher frequency of functional gastrointestinal disease in women, including IBS and intestinal constipation (23,24) .…”
Section: Discussionsupporting
confidence: 81%
“…Our study found that the lactose intolerant women presented a greater frequency for gastrointestinal symptoms than men. Similar results were evidenced in a Dutch study (21) , in which from a sample consisting of 16.758 individuals, 26% reported having gastrointestinal symptoms with a high prevalence of females (66%), and also in a Brazilian study by Del'Arco and collaborators (22) . Differences between the sexes in intestinal motility and visceral sensibility have already been suggested in the literature as factors associated with the higher frequency of functional gastrointestinal disease in women, including IBS and intestinal constipation (23,24) .…”
Section: Discussionsupporting
confidence: 81%
“…Del' Arco (27) found in their study that gastrointestinal diseases, including constipation, negatively impact different elements of quality of life in Brazilian women, such as mood, concentration and sexuality, so studying the prevalence and correct management of this condition is important. Thus, this study seeks to contribute by identifying factors which are related to IC and to support planning actions aimed at patients suffering from constipation through these findings, thus improving the care provided by health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity in this study was not associated with the IC prevalence, and this may have happened because only physical activity was evaluated, not physical exercise. However, physical activity and proper nutrition appear as important actions to regulate gastrointestinal motility, as a high-fiber diet can increase stool weight, resulting in a shorter colon transit time, while a low-fiber diet leads to constipation (27) , while physical activity can increase propulsion movements in the large intestine (28) .…”
Section: Discussionmentioning
confidence: 99%
“…14 This finding corroborates a previous study which demonstrated a negative impact of gastrointestinal diseases, including constipation, on different elements of quality of life in Brazilian women such as mood, concentration and sexuality. 22 …”
Section: Discussionmentioning
confidence: 99%